ЗНАЧЕННЯ ГУМАНІТАРНИХ І РАЦІОНАЛЬНИХ НАУК У ПІДГОТОВЦІ НАУКОВИХ КАДРІВ (Zaporizhzhia Historical Review, 2021)
The article raise a question of transitional period in development of a Ukrainian High School. Consider the role in formation and perception of the humanitarian and rational knowledge in process of training of Ukrainian scientists in the 90-th of XX century. All material given according to the official statistics of the Ukrainian committee.